Exploring the Relationships Among Reading Engagement, Enjoyment, Perceived Competence, Perceived Difficulties and Reading Achievement - Totaj, Gjylë (Sodobna pedagogika, 2024)
: This research sought to investigate the relationships among and impact of reading engagement, reading satisfaction, perceived reading difficulty, perceived reading competence and Program for International Student Assessment (PISA) reading achievement. The data were collected from the PISA 2018 assessment. A total of 5058 students (2457 females and 2601 males) in 224 schools participated, representing 25,739 15-year-old students in Kosovo. These students were in the eighth, ninth, tenth, eleventh and twelfth grades. The dependent variably used in this paper included the score achieved by Kosovar students in reading in PISA 2018 (353 points). The independent variables included items from the PISA 2018 student questionnaire: questions on the index of teacher stimulation of reading engagement, the index of enjoyment of reading, perceptions of reading competence and perceived difficulty in reading. The International Association for the Evaluation of Educational Achievement (IEA), International Database (IDB) Analyzer was used in analysing the data. Correlation and regression analyses were performed to assess the correlations and interactions between the stimulation of reading engagement, reading satisfaction, the perception of reading competence, perceived reading difficulty and PISA reading achievement. While some factors exhibited a weaker influence, others, such as the enjoyment of reading and the perception of reading competence, were significantly associated with reading performance. The findings indicate that educators and policymakers play an important role in fostering a culture of reading and improving reading achievement among students in Kosovo.
Keywords: bralna pismenost; bralna zavzetost; branje; competences; education; kompetenca; learning; pedagogika; pedagogy; PISA; pupils; reading; reading approach; reading literacy; učenci; učenje; vzgoja in izobraževanje